Thermistors and stacked thermopile on III-nitride LED wafer and their application for on-chip temperature measurement - Jing Tong; Jiabin Yan; Li Fang (AIP Advances, 2024)
Temperature measurement of devices in working state is of critical importance. In this work, GaN-based thermistors and a thermopile are monolithically integrated with a III-nitride blue light-emitting diode (LED) for the on-chip temperature measurement of the LED. The thermistor is based on the temperature-dependent resistance, and the stacked thermopile is based on the Seebeck effect. The measured results indicate that both thermistors and the thermopile can monitor the temperature of the LED sensitively. Due to the advantages of higher sensitivity and easier signal processing, the thermopile is more suitable for real-time monitoring.